2016
DOI: 10.1080/14999013.2016.1152613
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Therapy as an Additive Intervention for Violent Forensic Psychiatric Inpatients: A Pilot Study

Abstract: The first results of psychomotor therapy (PMT) as an additional component to Aggression Replacement Training (ART) were explored in a group of forensic psychiatric inpatients (N D 37). Patients were divided into two groups: ARTCPMT (experimental group) and ARTCSports (control group). Primary outcome measures of aggression, anger, and social behavior, and secondary outcome measures of coping behavior and bodily awareness during anger were administered on three occasions: pretreatment, posttreatment (after 35 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 57 publications
1
10
0
11
Order By: Relevance
“…These studies are limited because most comprise small participant populations and is unclear whether all participants have a history of violent offending, most participants in these studies were noted to be diagnosed with PD rather than SMI (e.g., Bernstein et al, 2012;Davidson et al, 2009;Doyle et al, 2016) or the participants were predominantly diagnosed with PD (Zwets et al, 2016). Finally, as noted above, none have evaluated the sort of multi-modal interventions that are now (relatively) common in criminal justice services and seen as necessary for high-risk violent offenders with multiple needs and internal responsivity issues (Polaschek, 2011).…”
Section: Violent Offender Treatment Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are limited because most comprise small participant populations and is unclear whether all participants have a history of violent offending, most participants in these studies were noted to be diagnosed with PD rather than SMI (e.g., Bernstein et al, 2012;Davidson et al, 2009;Doyle et al, 2016) or the participants were predominantly diagnosed with PD (Zwets et al, 2016). Finally, as noted above, none have evaluated the sort of multi-modal interventions that are now (relatively) common in criminal justice services and seen as necessary for high-risk violent offenders with multiple needs and internal responsivity issues (Polaschek, 2011).…”
Section: Violent Offender Treatment Effectivenessmentioning
confidence: 99%
“…Evaluations of Aggression Replacement Training have produced positive impacts on aggression and self-reported anger (Zwets, Hornsveld, Muris, Kanters, Langstraat, & van Marle, 2016), as have evaluations of the cognitive skills programme Reasoning and Rehabilitation, in terms of improvement in attitudes towards violence (Young, Gudjonsson, & Chick, 2010), and reduction in violent behaviour (Cullen, Clarke, Kuipers, Hodgins, Dean & Fahy, 2012).…”
Section: Violent Offender Treatment Effectivenessmentioning
confidence: 99%
“…supported our results by reporting that anger in a forensic population is inversely related to impulse control, especially in a hostility context. A high level of anger arousal is considered a determinant of impulsive behavior because anger arousal negatively impacts cognitive control processes 31,50 . The use of some cognitive‐behavioral approaches in psychosocial treatments is known to help individuals achieve better impulse control and improve their ability to evaluate the situation before reacting 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the power analysis, we found that 52 patients (26 in the experimental group and 26 in the control group) should be included in the study to achieve 80% power at a 0.05% significance level within a 95% confidence interval. We used the study by 31 “Psychomotor therapy as an additive intervention for violent forensic psychiatric inpatients: A pilot study” as a reference in the power analysis. The strength of comparison of Anger Rumination Scale (ARS) scores between the post‐experiment and control groups was 0.99, and the effect size was 2.06.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, CBT techniques and insight are given an extra context in which experiences and training with new forms of behaviour are part of the therapy sessions. Actively evoking here-and-now experiences is a basic principle in PMT (Boerhout et al, 2013;van der Maas et al, 2015;Röhricht, 2009;Zwets et al, 2016). PMT emphasises interoceptive awareness (being aware of changes in body signals) as opposed to placing emphasis awareness of the emotion of anger in an effort to enable individuals with MBID to reflect on the relationship between experiences and feelings (Kay et al, 2016).…”
mentioning
confidence: 99%